An efficient new iterative method for finding exact solutions of nonlinear time-fractional partial differential equations - Koçak, Hüseyin; Yıldırım, Ahmet (Nonlinear Analysis: Modelling and Control, 2011)
In this paper, a new iterative method (NIM) is used to obtain the exact solutions of some nonlinear time-fractional partial differential equations. The fractional derivatives are described in the Caputo sense. The method provides a convergent series with easily computable components in comparison with other existing methods.